Paramagnetic hard stainless steel and its manufacturing method
The development of a paramagnetic stainless steel with a hardness of 575 HV or higher, achieved through a heat treatment process without prior strain hardening, addresses the challenges of manufacturing high-hardness nonferromagnetic alloys, resulting in components with enhanced hardness, corrosion resistance, and aesthetic appeal.
Patent Information
- Application Number
- JP2023518759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-09
- Filing Date
- 2021-09-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-09-06
AI Technical Summary
Existing nonferromagnetic metal alloys with hardness exceeding 500 HV are rare and difficult to manufacture, as they often require prior strain hardening, which is challenging for complex shapes and costly in terms of machining and processing.
A paramagnetic stainless steel composition with a hardness of 575 HV or higher, achieved through a heat treatment process without prior strain hardening, utilizing a specific microstructure of austenite and sigma phases for enhanced hardness, toughness, and corrosion resistance.
The solution provides stainless steel parts with high hardness, excellent corrosion resistance, and good aesthetic appearance, suitable for applications in timing devices and other components exposed to mechanical and environmental stresses.
Smart Images

Figure 0007659053000001 
Figure 0007659053000002 
Figure 0007659053000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a paramagnetic stainless steel having a hardness of at least 575 HV and to a part made from this steel, in particular a timepiece component. The present invention further relates to a method for producing this stainless steel part. [Background technology]
[0002] Hard non-ferromagnetic metal alloys are used in many fields, primarily for components that are subject to high mechanical and / or tribological stresses and where it is essential that they are not subject to magnetic fields. This is particularly the case for many timekeeping components, such as gears, pinions, shafts or springs in movements. It is also important to obtain a high hardness for external parts, such as case middles, bezels, backs and crowns, since this generally results in better scratch and wear resistance and, therefore, better durability of these components exposed to the external environment.
[0003] In metallurgy, various mechanisms are used to harden alloys, depending on the alloy's chemical composition and thermodynamic history. In this regard, solid solution hardening, age hardening, strain hardening, martensitic transformation of steels, spinodal decomposition, and grain boundary strengthening (Hall Petch) are known. The most notable alloys use several of these hardening mechanisms simultaneously. However, non-ferromagnetic alloys with hardnesses above 500 HV are rare. Moreover, to achieve such high levels of hardness, crystalline non-ferromagnetic alloys generally require a high degree of strain hardening before an optional heat treatment to achieve maximum hardness by precipitation of a second phase. This is the case, for example, of austenitic stainless steels, which can only be hardened by strain hardening, or of some austenitic superalloys, which can be hardened by strain hardening followed by a precipitation heat treatment. In practice, it is difficult to manufacture components from these alloys in the strain-hardened temper. Firstly, in the case of forging, it is not straightforward to perform the appropriate degree of strain hardening to obtain the required hardness, especially for parts with complex geometries. Alternatively, machining can be performed on semi-finished products with a defined homogeneous strain hardening degree, but it is not always easy to obtain the appropriate material format with the required strain hardening degree. Moreover, any machining is very difficult and costly, since the alloys are already at least partially hardened. Finally, it is not possible to simply harden these alloys if the method used does not involve plastic deformation, such as certain powder metallurgy or additive manufacturing methods. Alternatively, it is possible to produce alloys with an intrinsic hardness of more than 500 HV, such as certain high entropy or intermetallic alloys, but these are similarly difficult to machine and almost impossible to deform, due to their very high hardness and very low ductility. This highlights the importance of finding alloys that are non-ferromagnetic in the hardened state, but can be hardened by heat treatment without the need for prior strain hardening. Thus, forming is performed in a soft and ductile state, and the hardening heat treatment is performed after the part is completed. It is for these reasons that carbon steels and martensitic stainless steels in particular have been very successful, although unfortunately the latter are ferromagnetic.
[0004] Other solutions are currently widely used to obtain hardnesses of more than 500 HV in non-ferromagnetic alloys. Various surface hardening processes are carried out, in particular for austenitic stainless steels or titanium alloys, for example after part forming. However, the thickness of the hardened layer is usually very small, of the order of a few tens of micrometers, and the appearance of the surface is usually altered by the treatment. Therefore, in the case of timepiece components, the parts have to be reworked after hardening in order to obtain a clean, all-over polished surface. However, such finishing operations remove all or part of the hardened layer, and this solution is rarely used in practice, especially since surface hardening treatments are generally expensive.
[0005] Thus, once again, there is a need to find non-ferromagnetic alloys that can be hardened by heat treatment to achieve hardnesses in excess of 500 HV. Summary of the Invention [Problem to be solved by the invention]
[0006] The aim of the present invention is to overcome the above mentioned drawbacks by proposing a stainless steel composition optimized to meet the following criteria: - paramagnetic behavior, - Hardness of more than 500HV, more specifically 575HV or more, achieved by heat treatment without the need for prior strain hardening during the manufacturing process; -Very good corrosion resistance.
[0007] It is essential that parts made from this steel also have a good aesthetic appearance, especially after polishing. [Means for solving the problem]
[0008] To this end, the stainless steel according to the present invention has the following composition by weight: - 20≦Cr≦40%, - 3≦Ni≦20%, - 0≦Mn≦15%, - 0≦Al≦5%, - 3 <Mo≦15%、 - 0≦W≦5%, - 0≦Cu≦2%, - 0≦Si≦5%, - 0≦Ti≦1%, - 0≦Nb≦1%, - 0≦C≦0.1%, - 0≦N≦0.5%, - 0≦S≦0.5%, - 0≦P≦0.1%, The remainder consists of iron and impurities, each at concentrations less than 0.5%.
[0009] According to the invention, the method for producing a stainless steel component consists of subjecting a substrate of the above composition in the ferritic or ferritic-austenitic field to a first heat or thermomechanical treatment, followed by quenching the material so as to retain the ferritic or ferritic-austenitic structure at ambient temperature. This ferritic or ferritic-austenitic microstructure is soft and therefore ductile, allowing easy forming if required. Then, after optional forming, a hardening treatment is performed to transform the ferrite into the austenitic and intermetallic sigma phases.
[0010] The novelty of the present invention comes, on the one hand, from the use of the sigma phase as a hardening source and, on the other hand, from a molybdenum content in the composition exceeding 3%. More specifically, the sigma phase has long been considered detrimental and therefore undesirable for stainless steels. The sigma phase is chromium-rich and generally forms at the grain boundaries, thus significantly reducing the corrosion resistance by reducing the chromium concentration of the other phases present in the alloy. The sigma phase embrittles stainless steels very quickly and substantially, even in very small amounts. This is because this phase has a complex tetragonal structure, is inherently very brittle, and its presence at the grain boundaries forms favorable paths for the propagation of cracks. Thus, the sigma phase has never been used in stainless steels, despite two particularly advantageous properties: a hardness of 900-1,100 HV10 and paramagnetic properties. According to the present invention, the composition of the stainless steel and the above-mentioned method are optimized to obtain a fine distribution of both the sigma phase and the austenite phase, without the dominance of the formation of the sigma phase at the grain boundaries. This particular microstructure of two non-ferromagnetic phases provides, among other things, an appropriate balance between hardness and toughness, excellent corrosion resistance, and excellent polishability.
[0011] Furthermore, a Mo content above 3% improves the corrosion resistance because a high Mo content results in a fairly high Mo concentration (>1%) in the austenite, even though Mo remains highly concentrated in the sigma phase. The presence of Mo increases the corrosion resistance of the austenite, improving the corrosion resistance of the alloy as a whole, more specifically the pitting corrosion resistance. A second advantage of having a Mo concentration above 3% is that it allows hardening heat treatments to be performed at higher temperatures in the γ+σ region, which further increases the Cr and Mo concentrations in the austenite, thereby further improving the corrosion resistance. Furthermore, performing heat treatments at high temperatures reduces the risk of forming carbides or nitrides that reduce the corrosion resistance. More specifically, the higher the temperature, the greater the solubility of carbon and nitrogen in the austenite.
[0012] Other features and advantages of the present invention will be better understood from the following detailed description when considered in conjunction with the drawings, in which: The figures in Figures 1 to 5 were created using the thermodynamic calculation software Thermocalc (TCFE10 database). [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a phase diagram of an Fe-(32.5-x)%Cr-7%Ni-x%Mo alloy (by mass%) showing the effect of Mo on the Sigma+CFC (austenite) phase field. [Diagram 2] FIG. 1 is a diagram showing the effect of hardening heat treatment temperature on the PREN of austenite for an Fe-28.5%Cr-7%Ni-4%Mo alloy (mass%). [Diagram 3] FIG. 1 is a phase diagram of a Fe-(29.5-x)%Cr-7%Ni-3%Mo-x%C alloy (wt%) according to the prior art, showing the effect of temperature on the solubility of carbon in the austenite phase. [Figure 4] FIG. 2 is a phase diagram of an Fe-(27.5-x)%Cr-7%Ni-5%Mo-x%C alloy (wt%) according to the present invention, showing the effect of temperature on the solubility of carbon in the austenite phase. [Diagram 5] FIG. 2 is a phase diagram of an Fe-(27.5-x)%Cr-7%Ni-5%Mo-x%N alloy (wt%) according to the present invention, showing the effect of temperature on the solubility of nitrogen in the austenite phase. [Figure 6] 1 is an image of an Fe-29.5%Cr-7%Ni-3.5%Mo steel (wt%) according to the present invention obtained by optical microscopy. [Figure 7] FIG. 1 shows current-potential curves of a potentiodynamic polarization test of an Fe-28.5%Cr-7%Ni-4%Mo steel (mass %) according to the present invention at three different hardening heat treatment temperatures, in comparison with an austenitic stainless steel DIN 1.4435 according to the prior art. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention relates to a paramagnetic stainless steel having a hardness of 575-900HV10, preferably 650-900HV10, more preferably 675-900HV10. HV10 hardness is understood to mean the Vickers hardness measured according to the ISO 6507-1:2018 standard. The present invention further relates to a part made with this steel, more specifically a component for a timepiece. The part may be an exterior part component selected from the group consisting of a case middle, a back cover, a bezel, a crown, a push part, a bracelet link, a bracelet, a tongue buckle, a dial, a clock hand, and a dial hour digit (not exhaustive). The part may also be a movement component selected from the group consisting of a gear, a shaft, a pinion, a spring, a bridge, a plate, a screw, and a balance (not exhaustive). The present invention further relates to the manufacture of a stainless steel part according to the present invention.
[0015] The stainless steel according to the present invention has the following composition by weight: - 20≦Cr≦40%, - 3≦Ni≦20%, - 0≦Mn≦15%, - 0≦Al≦5%, - 3 <Mo≦15%、 - 0≦W≦5%, - 0≦Cu≦2%, - 0≦Si≦5%, - 0≦Ti≦1%, - 0≦Nb≦1%, - 0≦C≦0.1%, - 0≦N≦0.5%, - 0≦S≦0.5%, - 0≦P≦0.1%, The remainder consists of iron and impurities, each at concentrations less than 0.5%.
[0016] Preferably, the stainless steel according to the invention has the following composition by weight: - 25≦Cr≦35%, - 5≦Ni≦10%, - 0≦Mn≦3%, - 0≦Al≦3%, - 3 <Mo≦10%、 - 0≦W≦5%, - 0≦Cu≦2%, - 0≦Si≦3%, - 0≦Ti≦1%, - 0≦Nb≦1%, - 0≦C≦0.1%, - 0≦N≦0.5%, - 0≦S≦0.5%, - 0≦P≦0.1%, Similarly, the remainder consists of iron and impurities.
[0017] Preferably, for one of the above composition ranges, the weight percentage of Mo is 3.5-15% or 3.5-10%. More preferably, the weight percentage of Mo is 3.5-6% or 4-6%.
[0018] Advantageously, within one of the above composition ranges, the weight percentage of W is between 0.2 and 5%, more advantageously between 0.5 and 5%.
[0019] A Mo content above 3 wt. % increases the concentration of Mo in the austenitic phase, which in turn leads to an increase in the overall corrosion resistance of the steel.
[0020] Furthermore, the increased Mo concentration allows the hardening heat treatment (in the sigma+CFC region) to be carried out at higher temperatures, particularly as shown in Figure 1. Thus, for 4% Mo the heat treatment can be carried out up to 950°C, and for 5% Mo up to 975°C. Carrying out the hardening heat treatment at higher temperatures in the sigma+CFC region further increases the Cr and Mo concentrations in the austenite, thereby further improving the corrosion resistance. The effect of treatment temperature on the PREN of austenite (pitting resistance index based on Cr, Mo and N content, e.g., PREN=%Cr+3.3x%Mo+16x%N) is shown in Figure 2.
[0021] Furthermore, performing the heat treatment at high temperatures reduces the risk of forming carbides or nitrides that reduce the corrosion resistance. More specifically, the higher the temperature, the greater the solubility of carbon and nitrogen in austenite. This effect is illustrated with respect to carbon using the phase diagrams in Figures 3 and 4 (for Fe-(29.5-x)%Cr-7%Ni-3%Mo-x%C alloy according to the prior art and for Fe-(27.5-x)%Cr-7%Ni-5%Mo-x%C alloy according to the present invention, respectively). Increasing the Mo concentration to above 3% allows the hardening heat treatment to be performed within the temperature range of 925-1,000°C, allowing the use of alloys with lower purity with respect to interstitial elements such as carbon and nitrogen, thereby dramatically reducing the cost of the alloy. In the case of 3% molybdenum in the Fe-(29.5-x)%Cr-7%Ni-3%Mo-x%C alloy in Figure 3, the γ+σ region is stable up to 925°C, and the maximum carbon concentration that prevents carbide precipitation (M23C6 phase in Figure 3) is only 0.01% above this temperature (see arrow in the figure). However, in the case of 5% molybdenum in the Fe-(27.5-x)%Cr-7%Ni-5%Mo-x%C alloy in Figure 4, the absence of carbides (M23C6 phase in Figure 4) is guaranteed at a temperature of 975°C up to a maximum carbon mass concentration of almost 0.02%, which is still within the γ+σ (CFC+Sigma) region. A small difference of 50°C in the hardening heat treatment is possible due to the higher Mo concentration, resulting in a two-fold difference in the solubility of carbides in austenite. The effect of temperature is similar for nitrogen, as shown for the Fe-(27.5-x)%Cr-7%Ni-5%Mo-x%N alloy in Figure 5. More specifically, the maximum nitrogen concentration to prevent nitride formation (HCP phase in Figure 5) increases significantly with temperature, from 0.15 wt.% at 925°C to about 0.3 wt.% at 975°C.
[0022] The stainless steel part according to the invention is manufactured using a method as further detailed below. According to the invention, the method for manufacturing a stainless steel part comprises the step (a) of providing or making a blank having a composition within the above range. The blank has a structure that is mostly ferritic, preferably 100% ferritic. The blank is obtained from a substrate subjected to a heat treatment or a thermomechanical treatment at a temperature in the range of 1,000 to 1,500 °C and then quenched. The substrate can be in powder form or in the form of a consolidated mass. The substrate can be manufactured by casting, pressing, metal injection molding (MIM), additive manufacturing and more generally powder metallurgy. It is envisaged that the substrate and the heat treatment can be carried out in a single step, for example by a selective laser melting (SLM) method. The various techniques mentioned above make it possible to make a blank with a substrate having dimensions substantially equal to those of the part to be made, in which case no subsequent forming step is necessary.
[0023] The composition of the substrate is optimized to obtain a mostly ferritic or fully ferritic structure when held at a temperature between 1,000°C and 1,500°C for a duration between 1 minute and 24 hours. The temperature is selected to obtain a mass fraction of austenite of less than or equal to 40% and a mass fraction of ferrite of more than or equal to 60%. The austenite formed when held at 1,000°C to 1,500°C is called primary austenite, in contrast to the secondary austenite formed in the subsequent hardening heat treatment. Preferably, the structure is fully ferritic after the hold at 1,000°C to 1,500°C.
[0024] Heat or thermomechanical treatments in the range of 1,000°C to 1,500°C can be used to homogenize, recrystallize or stress-relieve substrates obtained by casting or to sinter substrates in powder form. Treatments in the ferritic or ferritic-austenitic range can be carried out in a single cycle or can include several heat or thermomechanical treatment cycles, and can be preceded or followed by other heat or thermomechanical treatments.
[0025] After being held in the ferrite or ferrite-austenite field, the blank is quenched to a temperature below 500°C to prevent the formation of new phases during cooling. This is also known as quenching. In this way, the ferrite or ferrite-austenite structure is kept at ambient temperature. Thanks to the composition according to the invention, the ferrite structure is stable enough to be kept at ambient temperature after quenching, and is nevertheless metastable enough to be easily and rapidly transformed into sigma phase and austenite by subsequent heat treatment at intermediate temperatures between 600 and 1,000°C (see step (c) below).
[0026] At the end of step (a), the alloy has low hardness and high ductility, which may allow for easy shaping, for example by forging, blanking, or machining.
[0027] After step (a), the method includes an optional step (b) of forming a blank by any operation involving deformation, such as machining, blanking or forging. This step can be carried out in several sequences. If, at the end of step (a), the blank already has the final shape of the part to be manufactured, this step is not necessary.
[0028] In addition to forming, a plastic deformation operation can be carried out during the subsequent step of transforming the ferrite into austenite and sigma phase, in order to increase in particular the transformation rate of the ferrite. Furthermore, since the hardening due to strain hardening is low in the case of a ferritic structure and the alloy according to the invention is mostly ferritic or fully ferritic before the treatment by hardening, this plastic deformation step does not cause hardening that may be problematic in the optional forming by machining or blanking. This plastic deformation, carried out in one or more sequences, can be carried out at temperatures below 650°C.
[0029] After the optional forming operation, the method includes a step (c) of subjecting the blank to a hardening heat treatment in one or more stages between 600 ° C and 1,000 ° C to obtain the final properties. The duration of the heat treatment between 600 ° C and 1,000 ° C is fixed so as to ensure a complete transformation of the ferrite, resulting in a microstructure formed by sigma and austenite phases. Complete transformation is understood to mean that more than 99% of the ferrite is transformed into austenite + sigma phase. The final structure may therefore contain traces of residual ferrite in a proportion of less than 1%. As mentioned above, the rate of transformation of ferrite into austenite + sigma phase depends, inter alia, on the composition of the alloy and its thermomechanical history. Generally, the total duration of the heat treatment in one or more stages is between 30 minutes and 24 hours. Advantageously, the heat treatment is carried out in two stages, a first stage between 600 ° C and 850 ° C and a second stage between 850 ° C and 1,000 ° C. The cooler first stage results in faster transformation rates and a finer microstructure, while the hotter second stage maximizes resistance to corrosion. Because transformation is complete after the first stage, the microstructure remains fine after the hotter second stage.
[0030] After this hardening treatment, the steel has a mass fraction of 40-80% sigma phase and 20-60% austenite, these proportions depending on the chemical composition and the heat treatment carried out. As mentioned above, the steel may contain traces of residual ferrite in proportions of less than 1% by weight. The austenitic phase consists of secondary austenite and potentially primary austenite.
[0031] Advantageously, the primary and secondary austenite have a size of less than 10 μm, more advantageously less than 5 μm. This size is understood to mean the smallest dimension of the phase in a cross-sectional view. This may be the thickness of the austenite lamellae if the austenite is lamellar, or the diameter if the austenite is globular. In the latter case, the size relates to the smallest dimension of the austenite structure if the austenite is not perfectly globular.
[0032] Advantageously, the final structure is formed of secondary austenite and sigma phase without primary austenite. The resulting microstructure is a very fine and homogeneous eutectoid microstructure formed of secondary austenite and sigma phase. The secondary austenite is characterized by being finer than the primary austenite. This coarser structure of the austenite formed before hardening is not suitable for mirror finishing. Furthermore, the different composition of the austenite formed before and after hardening treatment is less favorable in terms of corrosion resistance.
[0033] The resulting parts have a high hardness of 575-900 HV10, more specifically 650-900 HV10, thanks to the hardening heat treatment. As with all stainless steels, small amounts of non-metallic inclusions can be present without affecting the mechanical and magnetic properties. Furthermore, inclusions such as manganese sulfides that improve machinability can also be present in small amounts in the alloy.
[0034] This hardening heat treatment step may optionally be followed by a surface finishing step (d), such as polishing.
[0035] Alternatively, in the presence of a blank having an austenite + ferrite structure in step (a), the manufacturing method can further include a step (b') of transforming the austenite + ferrite structure into a 100% ferrite structure in the temperature range of 100 to 1,500 °C prior to the hardening heat treatment.
[0036] In summary, by quenching after high-temperature heat treatment (1,000 to 1,500 ° C), the steel has, in particular, the following properties: ●Hardness of 150~400HV10 Good ductility with plastic deformation without cracking exceeding 50% under compression at ambient temperature • It exhibits ferromagnetic behavior due to the presence of ferrite.
[0037] After the hardening heat treatment, the steel according to the invention has in particular the following properties: ●Hardness of 575~900HV10 Paramagnetic behavior ●Excellent polishing properties due to extremely fine structure ● Extremely high wear resistance ●High corrosion resistance
[0038] In terms of corrosion resistance, the steels according to the invention are particularly effective thanks to their molybdenum concentrations of more than 3%, which increase the corrosion resistance of the austenitic phase and therefore the corrosion resistance of the entire alloy, making them particularly useful for external components.
[0039] Finally, the invention is illustrated by the following examples. EXAMPLES
[0040] Example 1 The steel known as Fe29Cr8Ni5Mo contains 58% iron, 29% chromium, 8% nickel and 5% molybdenum by mass. It is produced by arc melting from high purity elements (>99.9%) and cast in rod form. It is subjected to homogenization heat treatment at 1300 °C for 2 hours in argon atmosphere, followed by gas quenching (approximately 200 K / min). The rod is then deformed by compression at ambient temperature to reduce the thickness by a factor of 2, then annealed in air at 1080 °C for 10 minutes in the ferritic field and quenched in water. In this annealed state, the Fe29Cr8Ni5Mo alloy has a Vickers hardness of 265 HV10. A hardening heat treatment is then performed at 850 °C for one sample and at 900 °C for another sample for 6 hours. A fine homogeneous two-phase microstructure containing austenite and sigma phases is obtained. In this condition, the Fe29Cr8Ni5Mo alloy has a Vickers hardness of 705 and 675 HV10, respectively.
[0041] Example 2 The steel known as Fe29Cr7Ni4Mo contains 60% iron, 29% chromium, 7% nickel and 4% molybdenum by mass. This steel was also produced by arc melting from high purity elements (>99.9%), homogenized at 1300°C for 2 hours in argon, followed by gas quenching, deformed by compression to reduce the thickness by a factor of 2 at ambient temperature, annealed at 1100°C for 10 minutes in air, followed by quenching in water. After this annealing heat treatment, the Fe29Cr7Ni4Mo alloy has a single-phase ferritic microstructure. The first sample was then heated under vacuum at 700°C for 4 hours and then at 900°C for 3 hours. The resulting hardness is 670 HV10. The second sample was heated under vacuum at 750°C for 7 hours. The resulting hardness is 735 HV10. In either case, a fine two-phase microstructure is obtained.
[0042] Example 3 The steel known as Fe29.5Cr7Ni3.5Mo contains, by mass, 60% iron, 29.5% chromium, 7% nickel and 3.5% molybdenum. This steel was also produced by arc melting from high purity elements (>99.9%), homogenized at 1300°C for 2 hours in argon, followed by gas quenching, deformed by compression to reduce the thickness by a factor of 2 at ambient temperature, annealed at 1100°C for 15 minutes in air, followed by quenching in water. After this annealing heat treatment, the Fe29.5Cr7Ni3.5Mo alloy has a single-phase ferritic microstructure. The first sample was then heated under vacuum at 700°C for 4 hours and then at 900°C for 3 hours. The resulting hardness is 675 HV10. The second sample was heated under vacuum at 750°C for 7 hours. The resulting hardness is 730 HV10. The microstructure of the first sample observed by optical microscopy under polarized light is shown in Fig. 6. A fine distribution of two phases can be observed, with the austenite phase mainly in the form of raised lamellae and the sigma phase in the form of arrays.
[0043] Example 4 To evaluate the corrosion resistance in chloride media, especially the pitting corrosion resistance, potentiodynamic polarization tests were carried out on a commercial reference stainless steel (i.e. DIN 1.4435 steel) and on the Fe28.5Cr7Ni4Mo grade according to the invention, which underwent a hardening heat treatment at three different temperatures, namely 750, 800 and 850°C, respectively, for 6 hours under vacuum. The steel was previously heated in argon at 1,300°C for 2 hours and then cooled by gas quenching to obtain a 100% ferritic structure at ambient temperature. After the heat treatment at 750, 800 or 850°C, the alloy has a two-phase austenite + sigma phase structure. The potentiodynamic polarization measurements were carried out in an electrochemical cell with a saturated calomel reference electrode with potassium chloride and a platinum auxiliary electrode. The sample to be analyzed, i.e. the working electrode, is a disk of 8 mm diameter with a mirror finish. Potentiodynamic polarization tests were used to evaluate the corrosion resistance in chloride media by comparing the pitting potentials. The latter corresponds to the potential for localized rupture of the passive film and the rapid increase in the measured current as a result of pitting. For the purposes of the test, the pitting potential is defined as the potential corresponding to a current of 0.25 mA. First, a 1M NaCl solution is prepared and introduced into the cell, followed by nitrogen purging for 1 hour. The free potential Voc of the working electrode is recorded for 10 minutes. From the last free potential, the potential is increased at a rate of 0.5 mV / s to a measured current of 0.25 mA and then decreased at a rate of 2 mV / s to a measured current of 0.01 mA. The results are shown in Figure 7. An increase in the pitting potential with increasing heat treatment temperature can be clearly seen, with values of 0.32, 0.38 and 0.46 VvsSCE for heat treatments at 750, 800 or 850 °C, respectively, and 0.24 VvsSCE for the reference austenitic stainless steel. Furthermore, the repassivation of the potential-decreasing phase is promoted at higher heat treatment temperatures, which indicates that increasing Mo content is beneficial for increasing the heat treatment temperature and thus for increasing the corrosion resistance.
Claims
1. A paramagnetic stainless steel member, - 25≦Cr≦35%, - 5≦Ni≦10%, - 3<Mo≦10%, the remainder consisting of iron and impurities each having a concentration of 0.5% or less; The steel member has a hardness of 575 to 900 HV10 and a microstructure formed by 40 to 80 mass % of a sigma phase and 20 to 60 mass % of an austenite phase. steel parts.
2. The steel member according to claim 1, wherein Mo is 3.5% or more.
3. The steel member according to claim 1, wherein Mo is 3.5% to 6%.
4. The steel member according to claim 1, wherein Mo is 4% to 6%.
5. 2. The steel member according to claim 1, wherein the hardness is 650 to 900 HV10.
6. 2. The steel member according to claim 1, wherein the hardness is 675 to 900 HV10.
7. 2. A steel component according to claim 1, characterized in that the austenitic phase is formed by so-called secondary austenite, which results from the transformation of an alloy having a 100% ferritic structure.
8. 2. A steel component according to claim 1, characterized in that the austenite phase has a size of less than 10 μm, said size corresponding to the smallest dimension of said phase in a cross-sectional view.
9. 9. The steel component according to claim 8, wherein the austenite phase has a size of less than 5 μm.
10. A component made from the steel member of claim 1.
11. 11. Part according to claim 10, characterized in that it is an external part or a timekeeping component of a movement.
12. A watch including the timepiece component of claim 11.
13. A method for manufacturing a part made of paramagnetic stainless steel, comprising the steps of: (a) providing or producing a blank having substantially the shape of a part to be produced or differing in shape, said blank being made of, by weight: - 25≦Cr≦35%, - 5≦Ni≦10%, - 3<Mo≦10%, with the remainder consisting of iron and impurities each having a concentration of 0.5% or less, and having a predominantly ferritic or fully ferritic structure; (b) shaping the blank from step (a) if the blank has a different shape than the part to be produced; (c) subjecting said blank to a heat treatment, called hardening, to obtain said part having a hardness between 575 and 900 HV10, said hardening being carried out in one or more stages at a temperature between 600 and 1,000° C., for a total duration between 30 minutes and 24 hours, to transform the ferrite of said structure into 20-60% by weight of austenite phase and 40-80% by weight of intermetallic sigma phase, characterized in that said hardening is followed by cooling to ambient temperature; A method for producing a semiconductor device, comprising the steps of:
14. 14. The method according to claim 13, characterized in that the mostly ferritic or fully ferritic structure of the blank in step (a) is produced by subjecting the substrate to a heat or thermomechanical treatment at a temperature between 1,000 and 1,500°C for a duration between 1 minute and 24 hours, followed by quenching to a temperature below 500°C to preserve the ferritic structure at ambient temperature.
15. The method according to claim 13, wherein the heat treatment in step (c) is carried out in two stages, a first stage at 600°C to 850°C and a second stage at 850°C to 1,000°C.
16. The method according to claim 14, characterized in that the substrate is in the form of a powder or a solid.
17. The method according to claim 14, characterized in that the substrate is obtained by casting, pressing, metal injection molding or additive manufacturing.
18. The method of claim 17, wherein the blank in step (a) is produced by selective laser melting.
19. 14. The method according to claim 13, characterized in that the structure of the blank in step (a) contains a mass proportion of austenite of less than or equal to 40% and a mass proportion of ferrite of more than or equal to 60%.
20. The method according to claim 13, characterized in that the structure of the blank in step (a) contains 100% ferrite.
21. A method according to claim 13, characterized in that at the end of step (a), the blank has a hardness of 150 to 400 HV10.
22. The method of claim 13, wherein the forming step (b) comprises one or more plastic deformation sequences at a temperature below 650°C.
23. The method according to claim 13, characterized in that the forming step (b) is performed by forging, blanking or machining.
24. The method according to claim 14, characterized in that the thermal or thermomechanical treatment is carried out in several cycles.
25. 20. A method according to claim 19, characterized in that if the structure of the blank contains austenite, the method comprises, before step (c), a step (b') of subjecting the blank to a heat treatment or thermomechanical treatment at a temperature between 1,000 and 1,500°C for a duration between 1 minute and 24 hours to obtain a fully ferritic structure, said heat treatment or thermomechanical treatment being followed by a quench to a temperature below 500°C to preserve said fully ferritic structure at ambient temperature.
Citation Information
Patent Citations
Solid solution treatment of twoophase stainless steel
JP1981119721A
Superhard, tough nanocrystal austenitic steel bulk material having excellent corrosion resistance, and production method therefor
JP2004137599A